KNOWLEDGE MANAGEMENT AS A COMPETITIVE STRATEGY IN PT INDOSAT OOREDOO - Agustina, Granit (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
KNOWLEDGE MANAGEMENT AS A COMPETITIVE STRATEGY IN PT INDOSAT OOREDOO This study discusses Knowledge Management which is carried out in business organizations with the aim to find out the strategy in implementing knowledge management in PT Indosat Ooredoo. This study uses a qualitative method with a case study approach at PT Indosat Ooredoo. Data collection techniques in this study used observation, archival notes, interviews. From the results of the research that has been done, the following conclusions can be drawn: Knowledge management is carried out by creating a process based on information technology and virtual competence. Media technology supports information and communication that is intended to enhance the transfer of information and the overall sharing of organizational knowledge through cooperation and communication between individuals. Knowledge Management is very important as one form of organizational competitive strategy. The form of virtual communication in KM must also explore tacit knowledge. Key Words: Knowledge, knowledge management, storage of knowledge